Phonotactic Constraints in Young Cochlear Implant Recipients - Binos, Paris (My University, 2019)
Considerable attention has been paid to infant vocalization. The aim of the current research is to describe the prelinguistic vocal repertoire of seven young infants wearing cochlear implants and to argue for a strong relationship between early developmental stages of speech, as cochlear implantation seems to trigger similar vocal performances to hearing peers. In contrast to previous studies based on typical development, which argued for the existence of only one syllable type at each stage of linguistic speech, the present study recorded the simultaneous co-existence of multi-syllable types of protophones in populations characterized as atypical. Results support a gradual transition from babbling stages into mature, more complex forms of vocalization that we meet in adult speech. Protophonic development is rapid during the first post-implant year. The findings are in agreement with other studies based on typically developing children. The difference is that current data broaden the results to disordered populations, like infants with cochlear implants. The quantitative classification of protophones, through the combination of acoustic and auditory analyses, provides anew, reliable perspective for comparisons between populations with similar hearing experiences. Speech pathology targets to explore prelinguistic speech development and current methodologies to contribute to this direction. (PDF) Phonotactic Constraints in Young Cochlear Implant Recipients. Available from: https://www.researchgate.net/publication/333782313_Phonotactic_Constraints_in_Young_Cochlear_Implant_Recipients [accessed Mar 14 2023].
Keywords: cochlear implant; protophones; phonotactic; repertoire; prelinguistic